558 PREVALENCE AND IMPACT OF FRAILTY IN PATIENTS HOSPITALISED WITH COVID-19. THE SALFORD EXPERIENCE IN WAVES 1 AND 2. (14th June 2021) - Khan, A; Espinoza, F R; Kneen, T; Dafnis, A; Allafi, H; Carter, B; Narro-Vidal, M; Short, R; Price, A; Upton, R; Vilches-Moraga, A
Abstract: Introduction: The COVID-19 pandemic has had an extensive impact on the frail older population, with significant rates of COVID-related hospital admissions and deaths amongst this vulnerable group. There is little evidence of frailty prevalence amongst patients hospitalised with COVID-19, nor the impact of frailty on their survival. Methods: Prospective observational study of all consecutive patients admitted to Salford Royal NHS Foundation (SRFT) Trust between 27th February and 28th April 2020 (wave 1), and 1st October to 10th November 2020 (wave 2) with a diagnosis of COVID-19. The primary endpoint was in-hospital mortality. Patient demographics, co-morbidities, admission level disease severity (estimated with CRP) and frailty (using the Clinical Frailty Scale, score 1–3 = not frail, score 4–9 = frail) were collected. A Cox proportional hazards regression model was used to assess the time to mortality. Results: A total of 693 (N = 429, wave 1; N = 264, wave 2) patients were included, 279 (N = 180, 42%, wave 1; N = 104, 38%, wave 2) were female, and the median age was 72 in wave 1 and 73 in wave 2. 318 (N = 212, 49%, wave 1; N = 106, 39%, wave 2) patients presenting were frail. There was a reduction in mortality in wave 2, adjusted Hazard ratio (aHR) = 0.60 (95%CI 0.44–0.81; p = 0.001). There was an association between frailty and mortality aHR = 1.57 (95%CI 1.09–2.26; p = 0.015). Conclusion: Frailty is highly prevalent amongst patients of all ages admitted to SRFT with COVID-19. Higher scores of frailty are associated with increased mortality.